Clinical, electrophysiological and neuropsychological findings of twenty-two children with mesial temporal sclerosis - Aynaci, Fatma Müjgan; Ozdirim, Emire; Saatçi, Işil; Genç, Demet; Topçu, Meral; Turanli, Güzide; Topaloğlu, Haluk; Aysun, Sabiha (The Turkish Journal of Pediatrics, 2003)
Twenty-two patients, followed with the diagnosis of epilepsy between the ages of 8.5 and 19 years who were found to have mesial temporal sclerosis (MTS) on brain magnetic resonance imaging (MRI) were evaluated according to their clinical, electrophysiological and neuropsychological characteristics, and assessed for the significance of neuropsychological tests on lateralization. In both MTS groups, a remarkable number of patients had their intial seizure before one year of age (45.5% in the right MTS group, and 36.4% in the left MTS group). Half of the patients were seizure-free for a period of two months-9.5 years (average 3.9 years). The duration between the febrile seizure and first non-febrile seizure was 6.2 years. Eleven patients had MTS on the left temporal lobe. Interictal EEG was normal in five (22.5%) patients; 10 (45.5%) had temporal spike on the corresponding side with MTS. Six (27.3%) patients had paroxysmal activity and voltage asymmetry on cortical areas other than temporal region. The Wechsler Memory Scale (WMS), Visual Reproduction Subtest and Auditory Verbal Learning Test (AVLT) Delayed Recall and Retrieval Subtest performances were poor in the right MTS group.